The stage‐specific roles of radiotherapy and chemotherapy in nodular lymphocyte predominant Hodgkin lymphoma patients: a propensity score‐matched analysis of the SEER database. (28th November 2020) - Wang, Shijie; Jia, Mingfang; Han, Jianglong; Zhang, Rui; Huang, Kejie; Qiao, Yunfeng; Chen, Ping; Fu, Zhenming
Abstract: Background: The stage‐specific roles of radiotherapy (RT) alone, chemotherapy alone, and combined RT and chemotherapy (CRT) for patients with nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) have not been adequately evaluated. Methods: We analyzed patients with all stages of NLPHL enrolled in the Surveillance, Epidemiology, and End Results (SEER) registry from January 2000 to December 2015. Propensity score (PS) analysis with 1:1 matching (PSM) was performed to ensure the well‐balanced characteristics of the comparison groups. Kaplan–Meier and Cox proportional‐hazards models were used to evaluate the overall survival (OS), cancer‐specific survival (CSS), hazard ratios (HRs), and corresponding 95% confidence intervals (95% CI). Restricted mean survival times (RMST) were also used for the survival analyses. Results: For early‐stage patients, CRT was associated with the best survival, the mean OS was significantly improved by approximately 20 months (20 m), and the risk of death was reduced by more than 80%, both before and after PSM ( p  < 0.05). For advanced‐stage patients, none of RT alone, chemotherapy alone, or CRT had a significant effect on survival. Chemotherapy alone and CRT might be more beneficial for long‐term survival (RMST120 m : neither RT nor chemotherapy vs. chemotherapy alone vs. CRT = 104 m vs. 111 m vs. 108 m). Subgroup analysis of patients with early‐stage NLPHL showed that CRT was associated with better survival of elderly patients (improved OS = 43.8 m, HR = 0.14, p  < 0.05). However, the survival benefits of treatments for young patients were not statistically significant. The efficacy of RT was significantly different between the age groups ( p for interaction  = 0.020). Conclusions: These results from SEER data suggest that CRT may be considered for early‐stage NLPHL, especially for elderly patients. Further studies are needed to identify effective treatments in patients with advanced‐stage NLPHL. Abstract : Combined radiotherapy and chemotherapy (CRT) is associated with the best survival of patients with the early‐stage nodular lymphocyte predominant Hodgkin lymphoma (NLPHL). Timely intervention is beneficial to survival of patients with NLPHL, especially for elderly patients in early stages. For advanced‐stage NLPHL, chemotherapy alone and CRT are likely to be associated with the long‐term survival benefits.